Effectiveness of Gedong Gincu Mango Leaf Extract Gel (Mangifera indica L. var. Gedong gincu) on Cut Wound Healing in Male White Rats (Rattus norvegicus) of the Wistar Strain - Loren, Azzahro Maharani; Wirandoko, Ignatius Hapsoro; Marfuati, Sri (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: The Indonesia Basic Health Research data show the prevalence of wounds including incision/scratches/stab wounds reaches 20.1%. Natural herbal products play an important role in the wound healing process functioning as anti-inflammatories, antioxidants, antimicrobials, and collagen formation. Mango leaves are often considered waste even though they have many health benefits with the high content of coactive compounds, such as alkaloids, flavonoids, tannins, and saponins which are good for cut wound healing. The use of gel is more stable and controlled release compared to other topical preparations. Gedong Gincu mangoes originating from West Java have unique properties and they are marketed widely in some areas including Cirebon. Aims: This study aims to identify the most effective concentration of Gedong Gincu mango leaf extract on cut wound healing in male white rats (Rattus norvegicus) of the Wistar Strain. Methods: This study used a post-test-only control group design. The extract gel used three levels of concentration, namely 40%, 50%, and 60%. The positive control used 10% povidone iodine while the negative control used a gel base. The gel was applied to the cut wound twice a day for 14 days. Results: The average length of the cut wound was 0.916 cm, 0.912 cm, and 1.050 cm for concentration levels of 40%, 50%, and 60%. For the positive and negative controls, it reached 0.996 cm and 0.702 cm respectively. This indicates no significant difference in the length of the cut wound with a p-value of 0.121 (p>0.05). The wound healing process was effective at a concentration level of 60% as indicated by the disappearance of erythema and edema. Conclusion: Mango leaf extract gel (Mangifera indica L.var. Gedong Gincu) is effective in healing cut wounds with the disappearance of erythema and edema in male white rats (Rattus norvegicus) Wistar strain with a concentration of 60%. Received: 25 September 2024 | Reviewed: 19 October 2024 | Revised: 30 November 2024 | Accepted: 15 December 2024.